Effect of Energy Saving Technique on the Rate of Multiple Sclerotic Fatigue - Nasim Rasouli; Fazlollah Ahmadi; Seyyed Masoud Nabavi; Ebrahim Haji-Zadeh (University of Social Welfare and Rehabilitation Sciences, 2006)
Objective: Multiple Sclerosis is one of the most prevalent central nervous system demyelinization diseuse. Fatigue is a symptom of Multiple Sclerosis (MS). But indeed for the patients sometimes is so much more destroying than that. It is expected. Fatigue underlies and influences many of the other symptoms experienced by people with MS. To determine whether MS-Related fatigue, could be reduced after applying Energy Saving Techniques. Materials & Methods: This is a Quasi-experimental with Before-After Study design which was carried out in order to determine the effects of applying Energy Saving Techniques in the patients on MS-related Fatigue. These areas included Exercise, Rest & relaxation, Planning and Organization of daily activities, and body temperature control. Thirty nine convenient MS Patients were included and investigated over three months. Data collection tools included: demographic questionnaire, Fatigue Severity Scale (FSS), and self report checklists. Results: Data analysis shows decline in fatigue level after applying Energy Saving Techniques. The mean level of fatique before applying techniques was 5/36 and after that decrease to 4/58. Conclusion: According to these finding, applying Energy Saving Techniques reduces the fatigue of patients with Multiple Sclerosis.